Are the Children willing? Intergenerational Support for Marine Protected Area Sustainability - Oracion, Enrique G. (Silliman Journal, 2023)
The Apo Island "no-take" marine protected area (MPA) in Dauin, Negros Oriental, Philippines has remained consistently stable since the time it was directly man-aged by the community up to the present under the management of the Protected Area Management Board (PAMB). Based on the perceptions of grandparents, par-ents, and children, the future of this MPA also appears promising. However, the insignificant but consistent downward trends in the perception ratings of adults of MPA enforcement, compliance, biophysical conditions, and benefits imply some emerging resentments and cynicisms towards the current MPA management. Nevertheless, the absence of significant differences in perceptions in all these parameters by raters across generations suggests that intergenerational flow and sharing of MPA knowledge and realities are at work in which adults serve as infor-mation providers and role models to the children.